Lexical Features in the TED Talks "Future Education" : A Corpus-Based Approach - Tutut Indah Widyawati; Dita Farisa Setyo Budhi; Irma Khoirot Daulay; Toyyibah Toyyibah (Journal of Pedagogi, 2024)
This study analyzed Yılmaz Köylü's TED Talk on future education using a corpus-based approach to identify key lexical features and provide insights into its linguistic structure. The analysis involved transcribing the TED Talk and examining various linguistic metrics, including word frequency, document length, vocabulary density, readability, and collocations using Voyant Tools. The results indicated that the talk contains 2,740 words, with 706 unique forms, demonstrating a rich and varied vocabulary. Key themes such as education, technology, skills, creativity, and innovation were prominent, emphasizing their interconnected roles in shaping the future of education. The readability index corresponded to a 10th-grade level, making the content accessible to a wide audience. Additionally, the analysis revealed a high average number of words per sentence, indicating the use of complex sentence structures. Recommendations for improving readability included simplifying sentences by breaking longer ones into shorter, more concise statements. The study underscores the need to adapt education systems to meet the evolving demands of a rapidly changing world, with technology and creativity playing central roles.